Utilizing Information Systems to Drive Social Change Through Education - Martins, Agus; Prihatmojo, Agung; Basri, La; Anggraini, Diah Retno; Anam, Khoirul (Vocational: Journal of Educational Technology, 2025)
This article explores the role of information systems in driving social change through education in Indonesia. Adopting a qualitative approach and a case study design, this research investigates how information systems, including online learning platforms and technology-based academic management systems, contribute to improving the efficiency, quality, and accessibility of education. Data were collected through interviews with key stakeholders, including educators, administrators, and students, along with document analysis from selected schools and institutions. The findings reveal that the integration of these technologies has led to enhanced learning outcomes, greater administrative efficiency, and increased student engagement. However, challenges such as digital inequality, insufficient infrastructure, and resistance to change were also identified. The study concludes that while information systems hold significant potential for educational transformation, addressing these challenges is crucial for maximizing their impact. The implications of this research suggest that policy makers and educational leaders should prioritize investments in infrastructure, training, and inclusive strategies to ensure the equitable and effective use of technology in education. This study contributes to the broader understanding of how technological innovations can drive positive social change within educational contexts in developing countries.